Mengembangkan Sistem Penjualan Sampah (QR TRASH) - Munte, Mei Hotma Mariati (Jurnal Visi Pengabdian Kepada Masyarakat, 2024)
Abstract Trash is a very complicated problem for anyone who lives and gets activities in any environment. Trash can be very disturbing for students because they are not disciplined in throwing away trash. The government issued Government Regulation (PP) Number 27 of 2020 concerning Specific Trash Management, Law Number 18 of 2008 concerning Trash Management, and Government Regulation Number 81 of 2012 concerning Management of Household Trash and Household-Like Trash as one of their concrete steps. System development projects involve students, teachers, programmers, and other parties within the school who know about and are affected by the project. The problems being faced by partners are planned to be overcome by providing software in the form of a trash buying and selling application or also known as qr trash. An initial agreement between the school and the software developer is the main requirement for using the waterfall method. The system was developed by designing an application that can be installed on smartphone devices. The application designed is called qr – trash. This application can be accessed if the user has registered an account first. Account registration by users is carried out via “qr code”.